FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PREEKLAMSIA PADA IBU HAMIL TRIMESTER III DI WILAYAH KERJA RUMAH SAKIT GRAHA MANDIRI PALEMBANG 2024 - Fika Minata Wathan; Angel Seftia Ningsih; Intan Sari; Siti Aisyah (Jurnal Kajian Ilmiah Kesehatan dan Teknologi, 2025)
Preeclampsia is a pregnancy disorder that usually appears after 20 weeks of pregnancy. The factors related to the incidence of preeclampsia are diet, maternal characteristics, parity, knowledge, education, attitude, family history of hypertension, coverage of ANC visits, physical activity, rest patterns, and obesity. This research was conducted in the Working Area of GrahaMandiri Hospital Palembang from May – June 2024. This study uses an analytical survey method with a Cross Sectional approach. Sampling used the Accidental Sampling technique where all pregnant women in the third trimester who checked their pregnancy in the Midwifery Poly Room were 32 people at the time this study was conducted. The results of this study are that there is a significant relationship between obesity and preeclampsia with a p value of 0.003 where p < 0.05. And there was also a significant relationship between diet and preeclampsia with a p value of 0.009 where p < 0.05. Also, there was no significant relationship between the coverage of ANC visits and preeclampsia in the Graha Mandiri Hospital Palembang Work Area in 2024 with a p value of 1,000 where p > 0.05. The conclusion of this study is that obesity and diet have a statistically significant relationship with the incidence of preeclampsia. Meanwhile, the coverage of ANC visits does not have a significant relationship with the incidence of preeclampsia in the Working Area of Graha Mandiri Hospital Palembang in 2024.